Body Image and Disability : Fitting in When Your Body Does Not - Janet Ann, Fernandez; Rafidah Aga, Mohd Jaladin (University of Malaya Press, 2021)
Body image relates to how you think, feel and act towards your body, while body esteem relates to whether you are satisfied or value your body. Past studies on body image have revealed that negative body image perceptions may be in"uenced by one’s gender, age group, physical disability, mental disorder and/or physical illness. The first part of the chapter describes the definitions and theories related to body image and body esteem. The second part discusses the historical context and importance of body image. The final part of the chapter explains how body esteem affects people with different types of disabilities.